Ovarian Mixed Malignant Brenner-Mucinous Tumor with Signet Ring Cells - Baharak Khadang; Atilla Omeroglu (Case Reports in Pathology)
Mucinous carcinomas with signet ring cells in the ovary, particularly those composed predominantly of signet ring cells, are extremely rare, and in vast majority of cases, they represent metastasis from another site such as the stomach, appendix, pancreaticobiliary tract, bladder, and breast (Hristov et al., 2007, Kiyokawa et al., 2006, Vang et al., 2006, Young, 2006). Malignant Brenner tumor is also rare comprising less than 0.5% of ovarian carcinoma. Although mixed Brenner-Mucinous tumors are relatively common, the combination of a primary ovarian signet ring carcinoma with a malignant Brenner tumor is unique and to the best of our knowledge not previously reported in the literature.